OVERVIEW OF THE COMPLIANCE OF LABORATORY OFFICERS USING PPE AT BENGKULU CITY PRIVATE HOSPITALS - Bahar, Mardiyansyah; Aprilia, Defita (STIKes Mitra Keluarga, 2025)
Introduction: Personal protective equipment is a set of tools used to protect individuals by preventing exposure to hazards that may affect parts or the entire body while working. A series of actions taken to reduce work related accidents and occupational diseases is known as Occupational Safety and Health. This study aims to describe the level of compliance with the use of personal protective equipment among laboratory staff in private hospitals in Bengkulu City. Methods: The study used a descriptive approach with primary data. The sampling technique was total sampling. The sample consisted of laboratory staff from two private hospitals in Bengkulu City, totaling 16 personnel. Nine laboratory staff were from Gading Medika Hospital and seven from Rafflesia Hospital. The research was conducted from 12 February to 17 April 2025. Results: The sample included 16 laboratory staff from two private hospitals in Bengkulu City, with nine staff from Gading Medika Hospital and seven from Rafflesia Hospital. Most laboratory staff were women (75 percent) compared to men (25 percent). All staff showed compliant knowledge levels (100 percent). However, only 93.75 percent demonstrated compliant attitudes, while 6.25 percent were still non compliant. This indicates that high knowledge levels are not fully reflected in work attitudes. Conclusion: Most laboratory personnel comply with the use of personal protective equipment. A small proportion still show non compliance. This condition may be influenced by factors such as unequal training, work culture that does not emphasize adherence to standard procedures, limited availability of protective equipment, and persistent habits in the workplace.